Effect of Topical Noni (Morinda citrifolia L.) Extract Cream on Interleukin-1 and PDGF Expression in a Rat Incision Wound Model - Ariyanti Putri; Sri Priyantini; Eko Setiawan (Media Publikasi Cendekia Indonesia, 2026)
Wound healing involves complex biological processes influenced by inflammation and tissue regeneration, where excessive interleukin-1 (IL-1) activity can delay recovery, while platelet-derived growth factor (PDGF) plays a pivotal role in fibroblast proliferation and collagen deposition. This study aimed to evaluate the effect of topical Noni (Morinda citrifolia L.) extract cream on IL-1 levels and PDGF expression in incised skin tissue. A post-test only control group design was conducted using 30 male Wistar rats randomly allocated into five groups: healthy control, negative control with basic cream, positive control with povidone iodine, treatment with 15% Noni cream, and treatment with 30% Noni cream. Incised wounds were created on the dorsal skin and treated once daily for seven days, followed by analysis of IL-1 using ELISA and PDGF expression using RT-qPCR. Statistical analysis showed no significant differences among groups (p=0.088 for IL-1; p=0.056 for PDGF), yet descriptive results revealed lower IL-1 levels in the 30% Noni group and higher PDGF expression in the 15% group, while povidone iodine produced the least favorable outcomes. These findings suggest a dose-dependent dual action of Noni extract cream, with the 30% formulation tending to attenuate inflammation and the 15% formulation enhancing regenerative activity. These findings descriptively showed the lowest IL-1 levels, although the difference was not statistically significant. Within the limitations of this study, topical Noni extract cream demonstrates potential as a safe and natural adjunctive therapy for wound management, warranting further investigation with larger sample sizes, extended observation periods, and histopathological confirmation